X-radiation effect on the vascularization of submaxillary gland - Espinal, E. G.; Schwint, Amanda E.; Itoiz, María Elina; Kurtzbart, R.; Perec, C. (1984)
Fil: Espinal, E. G. Comisión Nacional de Energía Atómica; Argentina